DYNAMIC BEHAVIOR ANALYSIS OF LOAD FREQUENCY CONTROL IN POWER SYSTEMS WITH HYBRID POWER PLANTS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
In power systems, maintaining a nearly constant frequency is essential for stable operation. The secondary control loop plays a crucial role in regulating the system frequency, ensuring it remains at or near its nominal value. Additionally, this control loop is responsible for maintaining the scheduled power exchange between interconnected control areas via tie lines. This study focuses on analyzing and simulating the dynamic response of interconnected power systems under various configurations. The examined power system areas include steam, hydroelectric, and gas power plants. MATLAB-based simulations are conducted on both two-area and three-area power system models. The time-domain simulation results are further evaluated through eigenvalue analysis of the system matrix under different operating conditions. The findings indicate that, following a step change in load demand within isolated areas, gas power plants exhibit the smallest frequency deviation (droop). In contrast, hydroelectric plants demonstrate the largest frequency droop. Additionally, gas power plants exhibit fewer changes in response to load changes compared to the other two types of generation sources.
Keywords: Interconnected power system; Steam power plant; Gas power plant; Hydro power plant; Load frequency control